Environmental influence on the phytochemical composition of Calligonum leucocladum populations in Kazakhstan - Mussina, M.; Tynybekov, B.; Öz, G.; Ydyrys, A.; Nurtayeva, M.; Imanaliyeva, M. (International Journal of Biology and Chemistry, 2025)
Calligonum leucocladum (Polygonaceae) is a characteristic shrub of arid and semi-arid regions of Central Asia, where plant survival is limited by scarce water and extreme temperature fluctuations. This study investigated the phytochemical profiles of three spatially separated populations of C. leucocladum collected from natural habitats in Kazakhstan. The results demonstrated the presence of various phenolic compounds, organic acids, and amino acids. Among them, artepillin C and caffeic acid phenethyl ester (CAPE) were detected in this species for the first time. Distinct differences in metabolite accumulation between populations were recorded. In particular, individuals from population P3, located in semi-arid mountainous terrain at an altitude of about 800 m above sea level, were characterised by increased concentrations of phenolic compounds, soluble carbohydrates and the osmoprotective amino acid proline. These population - specific metabolic features probably reflect biochemical adaptations to contrasting environmental influences. These results indicate that C. leucocladum is a valuable source of biologically active compounds, and variations in the composition of its metabolites are closely related to habitat conditions. Keywords: Calligonum leucocladum, phenolic compounds, artepillin C, proline, pharmacological potential, metabolic adaptation.